THE VIOLATIONS OF THE COOPERATIVE PRINCIPLES IN 'EASY MANDARIN' YOUTUBE CHANNEL CONVERSATIONS - Annisa Annisa; Ayesa Ayesa; Tri Wahyu Retno Ningsih (UIN Raden Mas Said Surakarta, 2025)
This study analyzes the violations of the cooperative principles in the YouTube channel Easy Mandarin as such violations in social media content reflect authentic language use and provide valuable insights into real world communication and pragmatic language learning. The main objective of this research is to identify how violations of the maxims of quantity, quality, relevance, and manner occur and what factors influence them. The data were collected from the transcription of videos from the YouTube channel by documentation technique. The data consist of 15 interview-style street videos from Easy Mandarin: Learn Mandarin from the Streets episode which were selected based on the highest number of views, with each video having a duration of approximately 12 to 15 minutes. The results of the analysis show that, in violation of the maxim of quantity, respondents often provide information that is less in-depth or too little, even though the purpose of the conversation is to create a comfortable atmosphere. It is found that the use of humour, false statements, and innuendo, in violation of the quality maxim, reduced the accuracy and truthfulness of the information. Meanwhile, violations of the maxim of relevance were identified through avoidance of direct conversation, refusal to develop the topic, and assertion of personal views irrelevant to the question. Finally, the maxim of manner was violated by errors in answering, forgetfulness, anxiety, and the use of empathy, pleasantries, and secrets, all of which obscured the clarity and depth of the conversation. The findings indicate that various social, emotional, and personal factors influence the violation of these maxims, thereby affecting the communication flow in the conversation.